2012
DOI: 10.1179/1362171812y.0000000029
|View full text |Cite
|
Sign up to set email alerts
|

Properties of SnZn lead free solders bearing rare earth Y

et al.

Abstract: Rare earth (RE) Y has been incorporated into eutectic SnZn solders to study the wettability, mechanical properties, oxidation resistance, microstructures and thermal fatigue behaviours. The results indicate that adding trace amount of RE Y can remarkably improve the wettability of SnZn solders. When the content of RE Y is 0?06 wt-%, the tensile and shear forces of SnZn-xY solder joints give 24?1% and 27?2% increase after soldering. In addition, it is found that SnZn0?06Y has better oxidation resistance than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…稀土元素 Er [24] 和 Y [25] 对于 Sn3.8Ag0.7Cu 钎料也具有明显的改善作用, Er 的添加范围控制在 0.05%~0.25%, 稀土可以最大 限度的发挥改善性能和细化金属间化合物的作用, 而稀土 Y 的最佳添加范围是 0.1%~0.25%. 稀土元素 Er [26] 和 Y [27] 对 Sn9Zn 钎料也具有类似的改性作用, 同时对抗氧化性也有一定的帮助, 皋 利 利 [28] 针 对 含 稀 土 元 素 Pr, Nd 的 Sn3.8-Ag0.7Cu 钎料和焊点进行研究, 证明了适量添加稀土 元素可以降低液态钎料表面张力, 改善钎料的润湿 性, 另外拉伸-剪切和抗蠕变特性也得到显著的提高.…”
Section: 合金化unclassified
“…稀土元素 Er [24] 和 Y [25] 对于 Sn3.8Ag0.7Cu 钎料也具有明显的改善作用, Er 的添加范围控制在 0.05%~0.25%, 稀土可以最大 限度的发挥改善性能和细化金属间化合物的作用, 而稀土 Y 的最佳添加范围是 0.1%~0.25%. 稀土元素 Er [26] 和 Y [27] 对 Sn9Zn 钎料也具有类似的改性作用, 同时对抗氧化性也有一定的帮助, 皋 利 利 [28] 针 对 含 稀 土 元 素 Pr, Nd 的 Sn3.8-Ag0.7Cu 钎料和焊点进行研究, 证明了适量添加稀土 元素可以降低液态钎料表面张力, 改善钎料的润湿 性, 另外拉伸-剪切和抗蠕变特性也得到显著的提高.…”
Section: 合金化unclassified
“…The rare earth (RE) elements have been considered as vitamins of metals, because a tiny amount of RE elements can significantly improve the properties of alloys. Zhang et al [ 27 ] reported that the proper amount of Y can not only refine the structure of the Sn-Zn alloy but also improve the wettability and mechanical properties of the Sn-Zn/Cu solder joint and enhance the oxidation resistance of the solder alloy. Besides, as connecting material, the corrosion resistance of the solder plays a decisive role in the service life and safety of electronic products.…”
Section: Introductionmentioning
confidence: 99%